2013
DOI: 10.1111/ajt.12179
|View full text |Cite
|
Sign up to set email alerts
|

Renal Transplantation After Ex Vivo Normothermic Perfusion: The First Clinical Study

Abstract: Ex vivo normothermic perfusion (EVNP) is a novel method of preservation that restores circulation and allows an organ to regain function prior to transplantation. The aim of this study was to assess the effects of EVNP in kidneys from marginal donors. Eighteen kidneys from extended criteria donors (ECD) underwent a period of EVNP immediately before transplantation. Kidneys were perfused with a plasma free redcell based solution at a mean temperature of 34.6• C. The outcome of these kidneys was compared to a co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
194
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 294 publications
(195 citation statements)
references
References 23 publications
1
194
0
Order By: Relevance
“…Each kidney underwent EVNP for a period of 60 min using a technique that has previously been described in detail 6, 7, 8. In brief, the organs were perfused with a warmed (35.2°C), oxygenated plasma‐free red cell–based solution at a pressure of 75 mmHg.…”
Section: Case Reportmentioning
confidence: 99%
See 1 more Smart Citation
“…Each kidney underwent EVNP for a period of 60 min using a technique that has previously been described in detail 6, 7, 8. In brief, the organs were perfused with a warmed (35.2°C), oxygenated plasma‐free red cell–based solution at a pressure of 75 mmHg.…”
Section: Case Reportmentioning
confidence: 99%
“…Preservation techniques such as ex vivo normothermic machine perfusion (EVNP) can be used to resuscitate and assess the quality of the kidney before transplantation 5, 6, 7. In an earlier laboratory study, we assessed the quality of 22 human kidneys declined for transplantation primarily due to inadequate in situ perfusion using EVNP 3, 5.…”
Section: Introductionmentioning
confidence: 99%
“…In a porcine model, beneficial results were presented for kidneys perfused ex vivo under normothermic conditions 10,11 . The first clinical trial performed in 2013 demonstrated a lower rate of delayed graft function when kidneys retrieved from extended criteria donors were perfused for 1 hr immediately before transplant 12 .…”
Section: Introductionmentioning
confidence: 99%
“…In kidney transplantation, Nicholson and Hosgood have described a very low DGF rate of only 5.6% after NMP, despite the fact that they used marginal donors. 51 The rate of DGF in these 18 patients is significantly lower than the 20.8% seen in the Eurotransplant trial using HMP. 22 The OCS™ Liver PROTECT clinical trial is currently initiating and Peter Friend's group from Oxford and Birmingham has just published the results of a Phase I study with 20 patients showing that NMP for liver transplantation is safe and feasible.…”
mentioning
confidence: 66%